(untitled) - LaRocca, Rajani; Lee, Huy Voun (New York, NY, 2025)
"Equal parts emotional and informative, here is a worthy picture book about citizenship and naturalization. This thoughtfully crafted text precisely breaks down the process by which new residents apply for and acquire US citizenship"--
Includes bibliographical references.
Keywords: Juvenile literature; United States; Citizenship; United States; Naturalization; United States; Citizenship; Juvenile literature; Naturalization; United States; United States; Juvenile literature; Emigration and immigration; United States; Emigration and immigration; Picture books